An Equivalent Circuit Model for Semiparallel Plate Electrostatic Torsion Mirror. Issue 1 (6th December 2013) - Maruyama, Satoshi; Mita, Makoto; Isamoto, Keiji; Chong, Changho; Fujita, Hiroyuki; Toshiyoshi, Hiroshi
SUMMARY: An equivalent circuit model for a semiparallel plate electrostatic torsion mirror has been developed based on an electrical circuit simulator. An analytical model for the electrostatic torque has been translated into a nonlinear dependent current source as a function of the input voltages that interpret the drive voltages and the mirror angle. Use of the suspension width as a fitting parameter explained well the experimental results on frequency response and the mirror's static deflection. © 2013 Wiley Periodicals, Inc. Electron Comm Jpn, 97(1): 37–47, 2014; Published online in Wiley Online Library (wileyonlinelibrary.com ). DOI 10.1002/ecj.11486